Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2017
DOI: 10.1115/gt2017-63149
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Approach for Real Gas Simulations: Part II — Flow Simulation for Supercritical CO2 Centrifugal Compressor

Abstract: This paper is presented in two parts. Part I (Tabular fluid properties for real gas analysis) describes an approach to creating a tabular representation of the equation of state that is applicable to any fluid. This approach is applied to generating an accurate and robust tabular representation of the RefProp CO2 properties. Part II (this paper) presents numerical simulations of a low flow coefficient supercritical CO2 centrifugal compressor developed for a closed loop power cycle. The real gas tables presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…e thermodynamic property table ranges were 250-600 K with 301 nodes for temperature and 1-30 MPa with 301 nodes for pressure. e resolution of the physical property table is enough to meet the table independence requirement according to the investigations of Li et al [28] and Saxena et al [29].…”
Section: Numerical Modelmentioning
confidence: 99%
“…e thermodynamic property table ranges were 250-600 K with 301 nodes for temperature and 1-30 MPa with 301 nodes for pressure. e resolution of the physical property table is enough to meet the table independence requirement according to the investigations of Li et al [28] and Saxena et al [29].…”
Section: Numerical Modelmentioning
confidence: 99%
“…Concretely, substituting the impeller inlet parameters into Equations (10) and (14), and replacing the absolute Mach number by the relative one using Equation (8) yields…”
Section: Of 26mentioning
confidence: 99%
“…Kim et al [13] carried out a three-dimensional numerical study for a SCO 2 compressor stage to obtain fundamental data for the design optimization near the critical point and in the supercritical state. More related studies can be found in the references [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…15 Nikola 16 pointed out that at high flow rates, the acceleration of flow near the blade leading edge (LE) induces the thermodynamic parameters of SCO 2 to drop below the critical point, thus promoting two-phase region formation. Saxena 17 noticed that the two-phase zone in the impeller passage extended toward the streamwise direction as the mass flow rate increased. Rinaldi 18 found that the two-phase zone at the LE of the main blades extended toward the hub side as the compressor speed increased.…”
Section: Introductionmentioning
confidence: 99%